2010
DOI: 10.1007/jhep12(2010)083
|View full text |Cite
|
Sign up to set email alerts
|

Standard model vacua for two-dimensional compactifications

Abstract: We examine the structure of lower-dimensional standard model vacua for two-dimensional compactifications (on a 2D torus and on a 2D sphere). In the case of the torus we find a new standard model vacuum for a large range of neutrino masses consistent with experiment. Quantum effects play a crucial role in the existence of this vacuum. For the compactification on a sphere the classical terms dominate the effective potential for large radii and a stable vacuum is achieved only by introducing a large magnetic flux… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…In this case the potential is invariant under SL(2; Z) modular transformations and therefore the extrema of the potential must be at the stationary points of the complex structure, that is, τ = 1 or τ = 1/2 + i √ 3/2. In fact, as it is concluded in [60], only the latter allows for the existence of minima. However, if there are both P and AP boundary conditions the combined minimization of complex structure and radius becomes less trivial.…”
Section: Jhep06(2018)051mentioning
confidence: 85%
See 2 more Smart Citations
“…In this case the potential is invariant under SL(2; Z) modular transformations and therefore the extrema of the potential must be at the stationary points of the complex structure, that is, τ = 1 or τ = 1/2 + i √ 3/2. In fact, as it is concluded in [60], only the latter allows for the existence of minima. However, if there are both P and AP boundary conditions the combined minimization of complex structure and radius becomes less trivial.…”
Section: Jhep06(2018)051mentioning
confidence: 85%
“…Even though V is not minimized with respect to all the variables at the vacua of the theory, we will still call it potential. The conditions for AdS 2 vacua are (see [41,60] for details):…”
Section: The Sm On the T 2 Torusmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally one can consider compactifications on general Riemann surfaces. Those have been argued in [6,8] not to lead to new vacua. The same has also been argued to be the case of 1D vacua [7]) (quantum mechanics).…”
Section: Ads Casimir Sm Vacua In 3dmentioning
confidence: 98%
“…[6] Arkani-Hamed et al explored this deep infrared SM region by making the interesting exercise of exploring the possible vacua that could be obtained by compactifying the SM action to lower dimensions. They found that there is a richness of vacua, a real landscape of vacua, both with AdS and dS geometries in 3D and 2D (see also [7,8] for low < 3D SM compactifications). The potential for the moduli of the compactification is induced by the Casimir effect of the lightest particles of the SM.…”
Section: /4mentioning
confidence: 99%